Convergence Analysis of an Accelerated Iteration for Monotone Generalized α-Nonexpansive Mappings with a Partial Order. (2nd April 2019) - Chen, Yi-An; Wen, Dao-Jun
Abstract : In this paper, we introduce a new accelerated iteration for finding a fixed point of monotone generalizedα -nonexpansive mapping in an ordered Banach space. We establish some weak and strong convergence theorems of fixed point for monotone generalizedα -nonexpansive mapping in a uniformly convex Banach space with a partial order. Further, we provide a numerical example to illustrate the convergence behavior and effectiveness of the proposed iteration process.